EVALUASI PELAKSANAAN DISTRIBUSI RANTAI PASOK TERHADAP KETERSEDIAAN BAHAN MEDIS HABIS PAKAI DI UNIT DONOR DARAH PUSAT PMI TAHUN 2023 - Hani Putri Febriyanti (2024)
Distribution of Disposable Medical Equipment (BMHP) plays an important role in determining availability and quality of goods from their vulnerability to misuse in field. However, there are still many problems insufficient BMHP availability and still many stock vacancies, expired products, inappropriate orders and delivery delays. The PMI Central Blood Donor Unit is tasked with meeting BMHP needs of the Blood Donor Unit and Blood Banks have collaborated. This research aims to analyze implementation, supporting and inhibiting factors, efforts to overcome obstacles to distribution implementation. This research uses a qualitative design with data collection through observation, in-depth interviews, document study. The informants determined based on a purposive sampling method consisting of 6 informants. The research results show that distribution of BMHP at PMI Central Blood Donor Unit is not optimal. This is caused by several factors: there are untrained officers, there is a mismatch in SOPs, there is no stock, location of the warehouse is near the toilet, the front of the warehouse provides access to other rooms. To face these obstacles, efforts are needed such as: holding training, strengthening SOPs in accordance with Minister of Health Regulation Number 4 of 2014, arranging warehouses, and building exclusive access to warehouses.